Institutsional'nye bar'ery i vozmozhnosti: vliianie na razvitie sportivnoi infrastruktury i ekonomicheskii rost v promyshlennykh regionakh Rossii - Zharikov N. A., Valeev A. E. (Law, Economics and Management, 2025)
The development of sports infrastructure in Russia's industrial regions faces a number of institutional barriers, including administrative obstacles, legislative restrictions, and insufficient funding. However, there are also significant opportunities associated with public-private partnerships, import substitution initiatives, and local economic development. This article analyzes the key institutional factors influencing the formation and development of sports infrastructure.
Keywords: экономический рост; economic growth; спортивная инфраструктура; institutional barriers; sports infrastructure; industrial regions of Russia; institutional factors; институциональные барьеры; промышленные регионы России; институциональные факторы